THE HISTORY OF THE ORIGIN OF THE WORD PEDAGOGY AND THE USE OF MODERN TECHNOLOGIES WHEN TEACHING IT AS A SCIENCE (Conferencea, 2022)
This article is about the history of the origin and development of the science of pedagogy, the use of foreign experiences in teaching it as a science in our country, the technologies that can be used in the teaching process, and its application to the educational process.